AJARAN KAHARUDIN DI YAYASAN AL-MAGHFURULLAH KABUPATEN CIREBON, JAWA BARAT - Suhanah Suhanah (Harmoni, 2015)
This research employs case study method with qualitative approach. The purpose of this research is to figure out some information related to al-Maghfurullah Foundation cases consisting of: 1). Profile of al-Maghfurullah Foundation; 2). Its religious activities; 3). Chronology of al-Maghfurullah Foundation is considered as deviant religious teaching; 4). Government and stakeholders efforts in solving al-Maghfurullah Foundation cases. The result of research shows that Kaharudin as the leader of al-Maghfurullah Foundation and teacher undertakes some deviant religious teachings and practices that lead to social upheaval and issue Indonesian Ulema Council fatwa to handle development of Kaharudin’s teaching. It can be seen that no parties deal with this cases seriously, comprehensively, systematically, and continuously.